Knowledge and food habits of hypertensive adults after counseling using nutrition & hypertension flipchart at Tanjung Priok Public Health Center - Maria Olivia Regina; Didit Damayanti (AcTion: Aceh Nutrition Journal, 2024)
Hypertension is a non-communicable disease that affects approximately 22% of the global population, as reported by the World Health Organization (WHO) in 2019. It also affects adults and the elderly (63,49%) more than the younger population (13,22%). This study aimed to determine the differences in the knowledge and food habits of patients after counseling using nutrition and hypertension flipcharts. The research used a pre-experimental design with a one-group pretest-posttest. The research was conducted at the Tanjung Priok Public Health Center in 2022 with 30 outpatients with hypertension as respondents. Respondents who met the inclusion criteria were selected through accidental sampling. Knowledge levels were collected using questionnaires, and food habits were assessed using a food frequency questionnaire (FFQ). Statistical analysis of the data was performed using a paired t-test (80% CI). The results showed a significant increase in the knowledge scores of patients, from 76,67 to 93,00 after counseling using nutrition and hypertension flipcharts (p <0,001). After counseling, descriptive analysis showed a reduction in the number of respondents who frequently consumed high-sodium and high-saturated foods. It was concluded that the knowledge levels and food habits of patients with hypertension can improve after counseling using nutrition and hypertension charts.